French adaptation and validation of the Niigata PPPD Questionnaire: measure of severity of Persistent Postural-Perceptual Dizziness and its association with psychiatric comorbidities and perceived handicap - Meletaki, Vasiliki; Gobinet, Maélis; Léonard, Jacques; Elzière, Maya; Lopez, Christophe (Frontiers in Neurology, 2024)
Persistent Postural-Perceptual Dizziness (PPPD) is a functional vestibular condition. Despite being the most common chronic neuro-otologic disorder, it remains undertreated. The Niigata PPPD Questionnaire (NPQ), developed by Yagi et al. in 2019 to assess the severity of PPPD, could be a useful tool to help in the screening and diagnosis of this condition. This study aimed to validate a French version of the NPQ and make it an available assessment tool. Moreover, we aimed to understand the characteristics of PPPD patients better. The NPQ was translated and adapted into French. 50 PPPD patients, 50 patients with vestibular disorders without PPPD, and 50 healthy controls were included. They answered the adapted NPQ and additional questionnaires assessing trait (STAI) and state anxiety (HADS-A), depression (HADS-D) and handicap related to dizziness (DHI). The NPQ’s reliability was assessed by Cronbach’s alpha. Intergroup comparisons and multiple linear regressions were conducted to examine the characteristics of PPPD patients compared to vestibular patients and healthy controls, to validate NPQ’s reliability, and to explore the effect of clinical parameters and treatment with selective serotonin reuptake inhibitors. Receiver operating characteristic (ROC) curves were carried out to determine the diagnostic values of the NPQ total score and sub-scores. Relations between NPQ and reported handicap, depression and anxiety were evaluated by correlations between questionnaire scores. The internal consistency was high (>0.8) for all NPQ subscales and the total score. Intergroup comparisons showed a significantly higher NPQ total score and sub-scores in the PPPD group compared to the two others. The ROC curve analysis showed a significant, but poor, discrimination of NPQ (AUC = 0.664) and its subscales. DHI scores, depressive symptoms and trait anxiety were significantly higher in PPPD patients than in vestibular patients and healthy controls. State anxiety did not differ between patients with PPPD and vestibular patients without PPPD. Finally, there was a significant correlation between the NPQ and the DHI. Our study provides a better understanding of PPPD symptomatology and its assessment. It showed that the NPQ is a reliable tool that can assist in symptom assessment for a French-speaking population.